DISRUPTION OF HAIR FOLLICLE IMMUNE PRIVILEGE IN ALOPECIA AREATA: ENIGMATIC MECHANISMS AND EMERGING CONCEPTS - Simeonovski, Viktor; Dimova, Maja; Kostovski, Marko; Mitrova Telenta, Julija; Mircheska Arsovska, Elena; Labachevska Gjatovska, Liljana (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2025)
Immune privilege (IP) is a specialized immunological state that protects certain tissues, including the hair follicle (HF), from immune-mediated destruction. The maintenance of hair follicle immune privilege (HFIP) is crucial for uninterrupted hair growth and is mediated by several mechanisms. These include the downregulation of major histocompatibility complex (MHC) class I molecules, the secretion of immunosuppressive cytokines such as transforming growth factor-beta (TGF-β) and alpha-melanocyte-stimulating hormone (α-MSH), and the recruitment of regulatory immune cells that suppress pro-inflammatory responses. Additionally, the blood-hair follicle barrier limits immune cell infiltration, further preserving immune privilege. However, in alopecia areata (AA), HFIP collapses triggering an autoimmune attack against follicular structures. This breakdown is marked by increased antigen presentation, heightened expression of MHC class I and II molecules, and an influx of autoreactive cytotoxic CD8+ T cells. These T cells, particularly those expressing the NKG2D receptor, recognize stress-induced ligands on follicular keratinocytes and initiate a cytotoxic response. Interferon-gamma (IFN-γ) and interleukin-15 (IL-15) play central roles in amplifying inflammation by activating the JAK-STAT signaling pathway, further promoting immune cell infiltration and follicular destruction. Additional immune cells, including natural killer cells, dendritic cells, and macrophages, contribute to disease pathogenesis by enhancing antigen presentation and sustaining the inflammatory cascade. Given the central role of HFIP collapse in AA, therapeutic strategies aimed at restoring immune privilege represent a promising avenue for long-term disease management. Future research should focus on identifying key molecular regulators of HFIP and developing targeted interventions to re-establish immune tolerance within the hair follicle.
Keywords: alopecia areata; immune privilege; hair loss; hair follicle